Arabidopsis PCR2 Is a Zinc Exporter Involved in Both Zinc Extrusion and Long-Distance Zinc Transport([W]) - Song, Won-Yong (American Society of Plant Biologists, 2010)
Plants strictly regulate the uptake and distribution of Zn, which is essential for plant growth and development. Here, we show that Arabidopsis thaliana PCR2 is essential for Zn redistribution and Zn detoxification. The pcr2 loss-of-function mutant was compromised in growth, both in Zn-excessive and -deficient conditions. The roots of pcr2 accumulated more Zn than did control plants, whereas the roots of plants overexpressing PCR2 contained less Zn, indicating that PCR2 removes Zn from the roots. Consistent with a role for PCR2 as a Zn-efflux transporter, PCR2 reduced the intracellular concentration of Zn when expressed in yeast cells. PCR2 is located mainly in epidermal cells and in the xylem of young roots, while it is expressed in epidermal cells in fully developed roots. Zn accumulated in the epidermis of the roots of pcr2 grown under Zn-limiting conditions, whereas it was found in the stele of wild-type roots. The transport pathway mediated by PCR2 does not seem to overlap with that mediated by the described Zn translocators (HMA2 and HMA4) since the growth of pcr2 hma4 double and pcr2 hma2 hma4 triple loss-of-function mutants was more severely inhibited than the individual single knockout mutants, both under conditions of excess or deficient Zn. We propose that PCR2 functions as a Zn transporter essential for maintaining an optimal Zn level in Arabidopsis.